Kegagalan Ayub dalam Mendidik Anak-Anaknya dalam Parenting Kristen: Sebuah Studi Eksposisi - Endik Firmansah; Simon Simon (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2025)
This research focuses on the exposition of Job's failure in educating his children, as reflected in Job 1:4-5, with an analysis of weaknesses in terms of communication and spiritual approach. This research aims to explore how education that focuses more on rituals and less directly involves children in the spiritual learning process can impact their moral and spiritual development. This study uses a qualitative method with an exposition approach to the biblical text and combines references from the latest literature on child education and Christian parenting. The research results show that Job's weakness in communicating with his children caused them to lack understanding of personal responsibility for their sins and spiritual life. Job relied more on sacrifices to atone for his children's sins rather than directing them directly to understand their sin and repent. This research concludes that good communication, integration of spiritual values into daily life, and teaching about personal responsibility are the keys to building children's spiritual character. Thus, this research provides a practical contribution to Christian education, especially in facing the modern challenges faced by today's generation.